Living with Oil : Promises, Peaks, and Declines on Mexico's Gulf Coast - Breglia, Lisa, 1972- (Book collections on Project MUSE., 2013)
For decades, Mexico has been one of the world's top non-OPEC oil exporters, but since the 2004 peak and subsequent decline of the massive offshore oilfield - Cantarell - the prospects for the country have worsened. 'Living with Oil' takes a unique look at the cultural and economic dilemmas in this locale, focusing on residents in the fishing community of Isla Aguada, Campeche, who experienced the long-term repercussions of a 1979 oil spill that at its height poured out 30,000 barrels a day, a blowout eerily similar to the 2010 Deepwater Horizon disaster. Tracing the interplay of the global energy market and the struggle it creates between citizens, the state, and multinational corporations, this study also provides lessons in the tug-of-war between environmentalism and the lure of profits. In Mexico, oil has held status as a symbol of nationalist pride as well as a key economic asset that supports the state's everyday operations. Capturing these dilemmas in a country now facing a national security crisis at the hands of violent drug traffickers, cultural anthropologist Lisa Breglia covers issues of sovereignty, security, and stability in Mexico's post-peak future. The first in-depth account of the local effects of peak oil in Mexico, emphasizing the everyday lives and livelihoods of coastal Campeche residents, 'Living with Oil' demonstrates important aspects of the political economy of energy while showing vivid links between the global energy marketplace and the individual lives it affects.